Recurrent gastrointestinal bleeding arising from a jejunal arteriovenous malformation in a child with capillary malformation-arteriovenous malformation syndrome - Abigail K. Zamora; Jan Smogorzewski; Chadi Zeinati; Joseph M. Miller; Minnelly Luu; Danuta Nowicki; Dean M. Anselmo (Elsevier, 2020)
Capillary malformation-arteriovenous malformation (CM-AVM) syndrome is classically a RASA1 mutation with small CMs and either central nervous system or musculoskeletal AVMs. However, CM-AVM2 has recently been discovered, and is characterized by an EPHB4 mutation to the EPHB4-RAS-ERK pathway. The skin findings favor those of hereditary hemorrhagic telangiectasia with Bier spots and telangiectasias, and the presence of central nervous system and musculoskeletal AVMs mirror classic CM-AVM. To our knowledge, this is the first report of a visceral AVM in CM-AVM2 in the literature. The patient presented with recurrent gastrointestinal bleeds, and after an extensive workup culminating in diagnostic visceral angiography, was found to have a CM-AVM2 with a jejunal AVM.